Filterisasi Dan Pencegahan Penyebaran Informasi Hoaks Pada Kalangan Masayarakat Di Kelurahan Nusa Indah - Gromiko, Rovesca; Erwanda, Ega Silvia; Opsenere, Berly; Inayatullah, Kamila; Narti, Sri (Jurnal Kewirausahaan dan Bisnis, 2024)
The aim of this KKN activity is to increase understanding of filtering and preventing the spread of hoax information among the community in Nusa Indah Village, Ratu Agung District, Bengkulu City. The method used in this socialization activity consists of three stages, namely the planning stage, the preparation stage, and the implementation stage. The delivery of socialization material carried out by KKN students is one of the efforts or concrete steps of Dehasen University Bengkulu's participation with Nusa Indah Village, Bengkulu City. Socialization in a face-to-face manner and using media for presentations in the presentation of material by the KKN team with residents of RT.04 and RT.05 Nusa Indah Village, Bengkulu City. The results of KKN activities are education so that the community understands the characteristics of hoax news, is able to filter hoax news spread on social media, and the community is also able to prevent the spread of hoax news. Prevention of hoaxes on social media is becoming increasingly important, so that social harmony in the midst of national plurality can be maintained. The output produced from the final report of this program is in the form of a journal or article that will be uploaded and published in Abdimah KaKaNya Journal with the title Filtering and Preventing the Spread of Hoax Information Among Communities in Nusa Indah Village.